2021
DOI: 10.1101/2021.05.19.21257469
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

REGEN-COV Antibody Cocktail Clinical Outcomes Study in Covid-19 Outpatients

Abstract: Background: REGEN-COV antibody cocktail (casirivimab with imdevimab) rapidly reduced viral load and decreased medically-attended visits in the phase 1/2 portion of this trial; REGEN-COV, retains activity in vitro against emerging SARS-CoV-2 variants of concern. Methods: The phase 3 portion of this adaptive, randomized, master protocol, included 4,057 Covid-19 outpatients with one or more risk factors for severe disease. Patients were randomized to a single treatment of intravenous placebo, or various doses of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 17 publications
5
43
0
Order By: Relevance
“…We extend these findings by showing that escape variants can also be efficiently selected in vivo upon treatment with individual antibodies, independent of dosage or treatment setting (prophylaxis or therapy), whereas the REGEN-COV combination fully protects against development of such resistance. Importantly, we confirm these findings in humans; we investigated the genetic diversity of the entire spike protein across 4,882 samples from 1,000 outpatients or hospitalized patients with confirmed COVID-19 from ongoing phase 1-3 trials (Weinreich et al, 2020(Weinreich et al, , 2021; https://clinicaltrials.gov; NCT04666441, NCT04426695, and NCT04452318). Analysis of baseline and post-treatment sequence diversity in placebo and REGEN-COVtreated patients demonstrated that the non-competing antibody combination protects against selection of drug resistant variants.…”
Section: Introductionsupporting
confidence: 63%
“…We extend these findings by showing that escape variants can also be efficiently selected in vivo upon treatment with individual antibodies, independent of dosage or treatment setting (prophylaxis or therapy), whereas the REGEN-COV combination fully protects against development of such resistance. Importantly, we confirm these findings in humans; we investigated the genetic diversity of the entire spike protein across 4,882 samples from 1,000 outpatients or hospitalized patients with confirmed COVID-19 from ongoing phase 1-3 trials (Weinreich et al, 2020(Weinreich et al, , 2021; https://clinicaltrials.gov; NCT04666441, NCT04426695, and NCT04452318). Analysis of baseline and post-treatment sequence diversity in placebo and REGEN-COVtreated patients demonstrated that the non-competing antibody combination protects against selection of drug resistant variants.…”
Section: Introductionsupporting
confidence: 63%
“…19 The two-antibody combination reduces the risk of emergence of treatment-induced SARS-CoV-2 variants and retains neutralization potency in vitro against already-circulating variants of concern or interest (VOC/VOIs), including B.1.1.7 (alpha), B.1.351 (beta), P.1 (gamma), B.1.617 (delta), and B.1.427/429. [20][21][22][23] REGEN-COV has proven effective in treating COVID-19 outpatients 24,25 and is currently authorized in the U.S. under an emergency use authorization (EUA) for the treatment of mild-to-moderate COVID-19 and for postexposure prophylaxis in certain individuals exposed to or at high risk of exposure to a SARS-CoV-2-infected individual. 26,27 We conducted a phase 3, randomized controlled trial in asymptomatic household contacts of SARS-CoV-2-infected individuals to assess whether subcutaneous REGEN-COV 1200 mg (600 mg of each monoclonal antibody) may prevent infection and/or COVID-19 in this high-risk setting.…”
Section: Main Outcome(s) and Measure(s)mentioning
confidence: 99%
“…On 20 August 2021, Ronapreve received conditional marketing authorisation for the prevention and treatment of covid-19 in the UK 1. Ronapreve (REGEN-COV in the US) comprises two monoclonal antibodies, casirivimab and imdevimab, that target the SARS-CoV-2 spike protein to reduce the risk and severity of covid-19 in selected patients 2345. Although Ronapreve’s approval represents a welcome expansion in the armamentarium against covid-19, it also brings difficult questions about who should be eligible for treatment.…”
mentioning
confidence: 99%
“…The conditional marketing authorisation was based on two pivotal trials 234. The first randomised 4567 outpatients with covid-19 to placebo or intravenous Ronapreve 23.…”
mentioning
confidence: 99%
See 1 more Smart Citation